Acute barium toxicity from ingestion of “snake” fireworks - Rhyee, Sean H. (Springer-Verlag, 2009)
INTRODUCTION: Ingestion of fireworks has been infrequently reported in the medical literature. We describe a case of acute barium poisoning following firework ingestion. CASE REPORT: A 35-year-old male with a history of severe mental retardation presented with vomiting and diarrhea following ingestion of 16 small fireworks (“color snakes” and “black snakes”). His condition rapidly deteriorated and he developed obtundation, wide complex dysrhythmias, and respiratory failure. Approximately 12 hours following ingestion, his serum potassium level was 1.5 mmol/L with a serum barium level of 20,200 μg/mL (reference range<200 μg/L). The patient eventually recovered with ventilatory support and potassium supplementation. DISCUSSION: Although firework ingestion is uncommon, clinicians should be prepared for potentially severe complications. In the case of barium poisoning, treatment consists of potassium supplementation, along with respiratory and hemodynamic support.